TOKOH-TOKOH FEMINISME NOVEL LARUNG KARYA AYU UTAMI - Bunga Febrimora Hendri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2017)
This thesis aims to (1) to describe the character of profeminism in the novel Larung Ayu Utami, (2) describe the character of kontrafeminisme figure in Kulung novel by Ayu Utami. Based on data analysis, the female figure of profeminism is Yasmin, Simbah, and Shakuntala. Because the three figures are strong, courageous, idealistic and optimistic person in dealing with life problems and persistent in realizing their desires in accordance with their competence. Tokung Larung as the main character is a supporter of feminism ideas because Larunglah who work with the figure of profeminism to realize his wishes. So feminism in the novel of Larung is only an individual movement. Meanwhile, the figure of women who kontrafeminisme character Mother Larung, Cok and Laila. These figures are figures who do not support feminist ideas. Because these figures are a pessimistic figure, no desire, patient, loving, shy and dependent on men.